Malocclusion Generates Anxiety-Like Behavior Through a Putative Lateral Habenula–Mesencephalic Trigeminal Nucleus Pathway - Liu, Xin; Zhou, Kai-Xiang; Yin, Nan-Nan; Zhang, Chun-Kui; Shi, Ming-Hong; Zhang, Hong-Yun; Wang, Dong-Mei; Xu, Zi-Jun; Zhang, Jing-Dong; Li, Jin-Lian; Wang, Mei-Qing (Frontiers in Molecular Neuroscience, 2019)
Malocclusion is an important risk factor for temporomandibular disorder (TMD), a series of disorders characterized by dysfunction in the orofacial region involving the temporomandibular joint and jaw muscles. We recently showed that experimental unilateral anterior crossbite (UAC) produced masseter hyperactivity through a circuit involving the periodontal proprioception, trigeminal mesencephalic nucleus (Vme), and trigeminal motor nucleus (Vmo). Anxiety is a common complication in patients with TMD. The lateral habenula (LHb) is involved in emotional modulation and has direct projections to the Vme. Therefore, the present research examined whether UAC facilitates excitatory input from the LHb to the Vme and subsequently anxiety-like behaviors in rats. The LHb activation was evaluated by the electrophysiological recording, assessment of vesicular glutamate transporter-2 (VGLUT2) mRNA expression, and measurement of anxiety-like behaviors. The effects of LHb activity on Vme were evaluated by electrophysiological recording from Vme neurons and local changes in VGLUT2 protein density. UAC produced anxiety in modelled rats and increased neuronal activity in the LHb. VGLUT2 mRNA expression was also increased in the LHb. Further, VGLUT2-positive boutons were observed in close apposite upon parvalbumin-labelled Vme neurons. VGLUT2 protein expression was also increased in the Vme. Significantly, injection of VGLUT2-targeted shRNA into the LHb reduced the expression of VGLUT2 protein in the Vme, attenuated UAC-associated anxiety-like behaviors, and attenuated electrophysiological changes in the Vme neurons. In conclusion, we show that UAC activates the LHb neurons as well as the periodontal proprioceptive pathway to provide excitatory input to the Vme and produce anxiety in rats. These findings provide a rationale for suppressing activity of the LHb to attenuate both the physical and psychological effects of TMD.